Analysis of students design activities towards biomimicry conceptual design - Wan Omar, Wan Noor Faaizah; Abd Rahman, Khairul Aidil Azlin; Abdullah, Muhammad Firdaus Abong (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The creation of a new idea is crucial in many aspects of thinking. An improvement in method of thinking process these days has been producing a lot of novelty in design circumstances. Design thinking is often and very much influenced by design work. Nowadays, there are many research fieldworks use design thinking process to explain certain arising problems. In this study, we use Biomimicry as an approach to develop students’ design activities. Biomimicry study was highlighted when many solutions have been successfully implemented using this method in various fields of work nowadays. Biomimicry was originally formed by two different Greek root words which are “bios‟ meant life and “mimesis” which means imitate. Now, many have started to recognize the importance of inspirations of nature since a lot of researches have been conducted to understand. Conceptual framework is the basis of understanding in any study or research. This study will be utilising properties specified in the frame work which has been produced in developing the research methods. By using two aspects of study methods which are questionnaire and drawing test as a medium for experimentation and analysis.